The Peter Pan paradigm - Cohen, J Craig (BioMed Central, 2008)
Genetic and environmental agents that disrupt organogenesis are numerous and well described. Less well established, however, is the role of delay in the developmental processes that yield functionally immature tissues at birth. Evidence is mounting that organs do not continue to develop postnatally in the context of these organogenesis insults, condemning the patient to utilize under-developed tissues for adult processes. These poorly differentiated organs may appear histologically normal at birth but with age may deteriorate revealing progressive or adult-onset pathology. The genetic and molecular underpinning of the proposed paradigm reveals the need for a comprehensive systems biology approach to evaluate the role of maternal-fetal environment on organogenesis. You may delay, but time will not Benjamin Franklin USA Founding Father